Pengaruh Kualitas Produk, Persepsi Harga dan Suasana Toko Terhadap Kepuasan Pelanggan Paris Baguette - Andika Ahmad Haryono; Sinthon L. Siahaan (CV. ULIL ALBAB CORP, 2024)
This study aims to identify the effect of product quality, price perception and store atmosphere on Paris Baguette customer satisfaction. The population in this study are customers who buy at Paris Baguette PIM 3 during the January-March period. For the data collection technique used is the survey method by distributing questionnaires, using a sample of 200 respondents. Methods of data collection using questionnaires distributed to respondents. The data analysis method used is SEM-PLS using Smart-PLS 3 software to process data. The results showed that product quality had no effect on customer satisfaction, but other variables namely perception of price and store atmosphere showed significant and positive effect, effect on customer satisfaction.